Achieving levels of project management maturity in organization = Poziomy osiągania dojrzałości projektowej organizacji - Szpitter, Agnieszka A. (Zielona Góra: Faculty of Economics and Management Press)
The article demonstrates achieving levels of project management maturity and presents research company V on construction levels of project management maturity by the project team organization while creating a new collection of women?s clothing. The results relate to five areas: knowledge areas of design, build structures common processes, build a single methodology, the types of benchmarking and the use of the idea of continuous improvement within the company. Identify research gaps in the maturity of design and knowledge gaps in the test design company, which provides guidance and recommendations for the future.
Keywords: dojrzałość projektowa organizacji; poziomy dojrzałości projektowej; knowledge management; project management maturity